2005
DOI: 10.1080/08035320510043600
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysed milk in preterm infants: An open problem

Abstract: Further investigations addressing protein and mineral metabolism as well as long-term effects, including neurodevelopment, are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Rigo et al [ 31 ] and Szajewska et al [ 32 ] reported about the nutritional insufficiency of hydrolyzed protein formula for term and preterm infants. Zuppa et al [ 33 ] also had the same question in their study. In the present study, the patients with FI who switched to AAF for a short termdid not develop any adverse clinical sign or symptom during AAF feeding, and it showed improvement in the symptoms and signs of FI with proper body weight gain.…”
Section: Discussionmentioning
confidence: 76%
“…Rigo et al [ 31 ] and Szajewska et al [ 32 ] reported about the nutritional insufficiency of hydrolyzed protein formula for term and preterm infants. Zuppa et al [ 33 ] also had the same question in their study. In the present study, the patients with FI who switched to AAF for a short termdid not develop any adverse clinical sign or symptom during AAF feeding, and it showed improvement in the symptoms and signs of FI with proper body weight gain.…”
Section: Discussionmentioning
confidence: 76%
“…Data from Mihatsch et al 3 suggest that time to full enteral feeds is shorter when infants are fed a HW infant formula but its' use is tempered by concerns for nutritional adequacy. 4,22 Data from this study suggest that a pHW formula can be fed from the beginning without such concerns, a critical consideration in the early establishment of adequate enteral intakes in these underfed infants.…”
Section: Discussionmentioning
confidence: 87%
“…If there are possible nutritional benefits for using EHF for feeding infants after NEC, they should be weighed against possible disadvantages. 21 Indeed, these formulas have an energy density close to that of term formulas, in addition to usually low mineral and polyunsaturated fatty acid contents as compared with preterm formulas. Urinary nitrogen excretion is higher, 22 and calcium and phosphorus absorption and nitrogen retention are lower in preterm infants fed with hydrolysed formula compared with those fed with whole protein formula.…”
Section: Discussionmentioning
confidence: 93%